Islamic Ethical Value of Customary Basis of Marriage Proposal Application in Indonesia - Edy Sismarwoto (Institute of Medico-legal Publications Pvt Ltd, 2020)
This community legal observance in the field of Islamic marriage is based on the concept of good deeds which can be said to be deontologically valid. The approach is based on deon/obligations arising from the principles of Islamic life. This research method is an empirical method that looks at social reality and is carried out with an ethical approach to understanding the meaning of deeds in the marriage process. Philosophical analysis is used to analyze values in the conduct of the marriage process of Islamic societies in Indonesia. The results showed that in Indonesian Islamic society, marriage and marriage registration had become a community culture that had a philosophical value of worship. This happens because there is enculturation in the form of symbols of Islamic teachings that make it easier for people to recognize the value of an action. Proposal and registration of marriage has become the culture of the Islamic community with the symbol of halal and worship in marriage. Thus the community’s obedience to Islamic law and state law is not coercion carried out by state power, but is the legal culture of Islamic society.